Dynamic model of co2 removal using aspen hysys - Mohd Faridhwan, Mohamad Zulkapli (2013)
The objective if this study is to stimulate CO2 removal process by using Aspen HYSYS. The methodology of this study is divided into two phase. The first phase relates to the model development of steady state and the second phase related to dynamic simulation. In the first phase, the design data are collected from an industry. The simulation results are then compared to the available design data. The second phase basically involves equipment sizing that should be conducted before the dynamic modeling is developed. Validation of dynamic model and real plant data is considered based on normal condition. The abnormal simulation is then conducted by introducing disturbances and or faults in the process. As the conclusion, this simulation can be used as training and learning tools for engineers and operator, to understand the dynamic characteristic of CO2 removal process and also be able to use the simulation to improved performance of the CO2 removal process